Prognostic factors in recurrent or metastatic squamous cell carcinoma of the head and neck. Issue 6 (16th January 2019) - Mirabile, Aurora; Miceli, Rosalba; Calderone, Rosa Gioia; Locati, Laura; Bossi, Paolo; Bergamini, Cristiana; Granata, Roberta; Perrone, Federica; Mariani, Luigi; Licitra, Lisa
Abstract: Background: In clinical trials of recurrent and metastatic head and neck carcinoma, Argiris et al have identified prognostic factors for overall survival (OS) and progression‐free survival (PFS), weight loss, Eastern Cooperative Oncology Group performance status (ECOG‐PS), tumor primary site, tumor differentiation, prior radiotherapy, deriving a two‐group prognostic classification. This study evaluates Argiris's classification in "field‐practice" patients. Methods: The main analysis included 327 cases; a secondary analysis excluded 31 patients with oropharyngeal carcinoma (OPC) p16‐positive and/or human papilloma virus (HPV)‐positive. OS and PFS curves were estimated with the Kaplan‐Meier method; multivariable Cox analyses were also performed. Results: In the full series, OS was significantly different in patients with 0‐2 and ≥3 adverse features (median, 14 vs 10 months; P  = .03). PFS was statistically different in the two groups (median, 7 vs 5 months; P  = .02). At a multivariable analysis investigating additional prognostic features, site of relapse and disease‐free interval were significant predictors of OS and PFS. Conclusion: The Argiris's model was confirmed in a "field‐practice" population. Moreover, we found additional putative prognostic factors.